Patients Who Undergo Early Aseptic Revision TKA Within 90 Days of Surgery Have a High Risk of Re-revision and Infection at 2 Years: A Large-database Study. Issue 3 (20th March 2022) - Shen, Tony S.; Gu, Alex; Bovonratwet, Patawut; Ondeck, Nathaniel T.; Sculco, Peter K.; Su, Edwin P.
Abstract: Background: Early aseptic revision within 90 days after primary TKA is a devastating complication. The causes, complications, and rerevision risks of aseptic revision TKA performed during this period are poorly described. Questions/purposes: (1) What is the likelihood of re-revision within 2 years after early aseptic TKA revision within 90 days compared with that of a control group of patients undergoing primary TKA? (2) What are the indications for early aseptic TKA revision within 90 days? (3) What are the differences in revision risk between different indications for early aseptic revision TKA? Methods: Patients who underwent unilateral aseptic revision TKA within 90 days of the index procedure were identified in a national insurance claims database (PearlDiver Technologies) using administrative codes. The exclusion criteria comprised revision for infection, history of bilateral TKA, and age younger than 18 years. The PearlDiver database was selected for its large and geographically diverse patient base and the availability of outpatient follow-up data that are unavailable in other databases focused on inpatient care. A total of 481 patients met criteria for early aseptic revision TKA, with 14% (67) loss to follow-up at 2 years. This final cohort of 414 patients was compared with a control group of patients who underwent primary TKA without revision within 90 days. For the control group, 137, 661 patients underwent primary TKA without early revision, with 13% (18, 138) loss to follow-up at 2 years. Among these patients, 414 controls were matched using a one-to-one propensity score method; no differences in age, gender, and Charlson comorbidity index score were observed between the groups. Indications for initial revision and 2-year re-revision were recorded. The Kaplan-Meier method was used to assess survival between the early revision and control groups. Results: Two-year survivorship free from additional revision surgery was lower in the early aseptic revision cohort compared with the control (78% [95% confidence interval 77% to 79%] versus 98% [95% CI 96% to 99%]; p < 0.001). Among early revisions, 10% (43 of 414) of the patients underwent re-revision for periprosthetic infection with an antibiotic spacer within 2 years. The reasons for early aseptic revision TKA were instability/dislocation (37% [153 of 414]), periprosthetic fracture (23% [96 of 414]), aseptic loosening (23% [95 of 414]), pain (11% [45 of 414]), and arthrofibrosis (6% [25 of 414]). Early revision for pain was associated with higher odds of re-revision than early revisions performed for other all other reasons (44% [20 of 45] versus 29% [100 of 344]; odds ratio 2.0 [95% CI 1.0 to 3.7]; p = 0.04) . Conclusion: Acute early aseptic revision TKA carries a high risk of re-revision at 2 years and a high risk of subsequent periprosthetic joint infection. Patients who undergo an early revision should be carefully counseled regarding the very high risk of repeat revision and discouraged from having early revision unless the indications are absolutely clear and compelling. Early aseptic revision for pain alone carries an unacceptably high risk of repeat revision and should not be performed. Adjunctive measures for infection prophylaxis should be strongly considered. Specific interventions to reduce surgical complications in this subset of patients have not been adequately studied; additional investigation of strategies to minimize the risk of reoperation or infection is warranted. Level of Evidence: Level III, therapeutic study.